Analysis of service waiting time and its impact on patient satisfaction at siloam hospitals Makassar - Petrus R. Lekay; Gracia Ongkowijoyo; Teofilus; Endi Sarwoko (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Hospital service efficiency plays a crucial role in shaping patient satisfaction, which is widely regarded as a key indicator of healthcare quality. Waiting time is one of the most frequently cited factors influencing patients’ perceptions of service performance. However, satisfaction is also affected by interpersonal aspects, such as professionalism and friendliness of healthcare staff. This study examines the relationship between service waiting time and patient satisfaction at Siloam Hospitals Makassar, focusing on registration, doctor, pharmacy, and cashier services. Methods: A quantitative research design was used, employing secondary data obtained from the MySiloam application. The study included 360 outpatients selected through purposive sampling. Independent variables consisted of waiting times for registration, doctor consultation, pharmacy services, and cashier processing, while patient satisfaction served as the dependent variable. Data were analyzed using the Chi-Squared Test to determine the relationship between waiting time categories and satisfaction levels. Results: The analysis showed no significant difference in registration waiting time between self–check-in users and those assisted by staff (ρ = 0.720). However, registration waiting time demonstrated a significant relationship with patient satisfaction (ρ = 0.009). In contrast, no significant associations were found between patient satisfaction and waiting times for doctor consultation (ρ = 0.202), pharmacy (ρ = 0.558), or cashier services (ρ = 0.831). Findings indicate that patients remain satisfied despite longer waits when services are delivered professionally and accurately. Conclusion: The study concludes that reducing registration waiting time may improve overall satisfaction, yet the interpersonal quality of healthcare services remains the most influential factor shaping patient perceptions and loyalty.These findings highlight the importance of enhancing both service efficiency and interpersonal service quality to strengthen patient perceptions and loyalty toward hospital services.